2013
DOI: 10.1088/0031-9155/58/5/1563
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional fluorescence tomography of human breast tissuesin vivousing a hand-held optical imager

Abstract: Diffuse optical imaging using non-ionizing radiation is a non-invasive method that shows promise towards breast cancer diagnosis. Hand-held optical imagers show potential for clinical translation of the technology, yet they have not been used towards 3D tomography. Herein, 3D tomography of human breast tissue in vivo is demonstrated for the first time using a hand-held optical imager with automated coregistration facilities. Simulation studies are performed on breast geometries to demonstrate the feasibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…A representative example of a mid-stage PoC technology is the implementation of fluorescence microscopy as a replacement for bright-field microscopy (10). Representative mid-stage PoP technologies include the handheld scanner for spectroscopic imaging of breast tumors and tissue for assessing treatment response (37, 51), as well as the array of optical techniques to evaluate the field effect of carcinogenesis during gastrointestinal imaging procedures (38). Late-stage technologies are those that have been widely evaluated in clinical trials and have been adopted by health care providers and integrated into health care systems.…”
Section: Screening Versus Diagnosticsmentioning
confidence: 99%
“…A representative example of a mid-stage PoC technology is the implementation of fluorescence microscopy as a replacement for bright-field microscopy (10). Representative mid-stage PoP technologies include the handheld scanner for spectroscopic imaging of breast tumors and tissue for assessing treatment response (37, 51), as well as the array of optical techniques to evaluate the field effect of carcinogenesis during gastrointestinal imaging procedures (38). Late-stage technologies are those that have been widely evaluated in clinical trials and have been adopted by health care providers and integrated into health care systems.…”
Section: Screening Versus Diagnosticsmentioning
confidence: 99%
“…The probe was used to demonstrate 2D target detection ) and co-registered imaging and 3D tomography (Erickson et al, 2013) in human subjects. The breast geometry was acquired using a commercially available scanner.…”
Section: Diffuse Optical Tomographymentioning
confidence: 99%
“…(b) The imaging setup where the initial 2D surface map is displayed in near real-time (mannequin shown for demonstration) (Erickson et al (2013),. (a) The system is composed of a laser diode source, a CCD camera detector, and the handheld probe (inset) that contains six source points (large dots) and 165 detection points (small dots).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive tissue phantom studies were performed to demonstrate 3D tomographic imaging capabilities of the imager (30, 35) as well as improved target depth detection (36). In vivo 3D tomographic breast imaging studies (on healthy subjects containing superficially placed tumor-like targets) were demonstrated using the hand-held optical imager (33). In parallel, a gen-2 version of the hand-held optical imager was also developed and its ability to detect targets was demonstrated in phantoms and human breast tissue (3738).…”
Section: Introductionmentioning
confidence: 99%